AI AND DIVERSITY IN SPORTS: OPPORTUNITIES AND CHALLENG: http://doi.org/10.46536/jpumhs/2024/14.02.526 - Hira Usman1, Shoaib Ahmed2, Naweera Ghaffar3, Anoosha Sajid4, Masooma Irfan51, Aamir Gul Memon6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
Memon6 The decision-making processes of coaches and athletes as well as the improvement of audience engagement have all been impacted by the integration of AI into the sports industry. Artificial intelligence (AI), especially generative AI, has emerged as a key player in influencing socioeconomic development in a number of international areas in recent years. There is no denying its influence; estimates indicate that it will increase at a rate of 19% per year and might reach $900 billion by 2026.